STUDY DESIGN LAMONG BAY RECLAMATION CONSTRUCTION USING GROUND IMPROVEMENT VIBRO COMPACTION AND PREFABRICATED VERTICAL DRAIN WITH FINITE ELEMENT METHOD - ANDRESON, REY
Breakwater structure is built on a reclamation area in Lamong Bay because the ground water level is high enough so the sand embankment must be supported by breakwater to make the embankment still stands in the staged construction. Because the subsoil consists of soft soil, the structure of the breakwater should be given the reinforcement so that the soil does not collapse, such as the construction of a bamboo matrass and bamboo cluster under the structure of the breakwater. Ground improvement in this reclamation area using Prefabricated Vertical Drain. triangular configuration with spacing of 1 meter. Construction of the sand embankment is done in stages so the embankment will not collapse and increase bearing capacity (gained strength) through the consolidation process. Because of the material of the embankment is sand, so there is a potential for liquefaction, therefore the embankment need the improvement using Vibro Compaction. PLAXIS 2D will give the model for finite element method and slope stability analysis. The results of slope stability analysis by PLAXIS 2D shown the embankment conditions, earthquakes, and service life meets the requirements of SF minimum value.